Trade liberalisation is good for you if you are rich - Charles Ackah; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
This paper investigates the relationship between trade policy and growth using a dynamic panel regression model with GMM estimates for data on 44 developing countries over 1980-1999. Trade policy is captured by measures of tariffs, import and export taxes. Typically, the average effects of changes in such policy variables have been investigated. However, from a policy perspective, the differential effects on highor low-income countries may be of more interest. Our preferred specification for growth thus includes as an explanatory variable an interaction term between trade barriers and initial income levels to capture the non-linearity in the relationship. This specification reveals a significant interaction effect under which the marginal impact of tariffs on growth is declining in initial income. In particular, for low-income countries tariffs appear to be associated with higher growth, whereas only for middleincome and richer countries is there a negative impact of tariffs on growth. The impact of a marginal change in protection on growth changes from positive to negative as income increases beyond a threshold level of GDP per capita (below which, in rough terms, a country would be classed as low-income). Put differently, trade liberalisation seems to offer the possibility of achieving faster growth only in relatively richer countries.
Keywords: F10; F14; O50; 330; Growth; Openness; Trade barriers; Cross-country analysis; Außenhandelsliberalisierung; Makroökonomischer Einfluss; Schätzung; Entwicklungsländer